The Effect Of Adding Andaliman Powder (Zanhtoxylum acanthopodium) On The Storage Of The Tempe Tempe Nugget - Evi Nursayanti Girsang; Tineke M. Langi; Maya Ludong (Jurnal Agroekoteknologi Terapan, 2022)
The purpose of this study was to analyze the effect of adding andaliman powder on the storage time of moringa tempe nuggets based on physical and microbiological quality. This study used a descriptive method consisting of 4 (four) treatments and 3 (three) replications with different andaliman addition treatments. Parameters tested were physical quality and total plate count analysis. The results showed that the addition of 2% and 4% andaliman powder was able to maintain the shelf life of Moringa tempe nuggets up to day 2 with ALT values of 1.4 × 104 and 2.8 × 103. The addition of 6% and 8% adaliman powder was able to maintain the shelf life of nuggets. Moringa tempeh until day 3 with ALT values of 1.2 × 103 and 8.7 × 102. Keywords: Nugget, Andaliman, Total Plate Count